SISTEM INFORMASI PENERIMAAN DONASI (STUDI KASUS: YAYASAN SAHABAT YATIM INDONESIA) - Muhamad Ikhsan Ibrahim; Wisti Dwi Septiani (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2017)
Sahabat Yatim foundation of Indonesia is an institution that is engaged in social-religious as an organization that plays an active role in providing care and coaching to orphans and poor children. It accommodates and distributes donations for orphans and the poor from donors. The main problem that is happening now is the making of less effective and efficient so that there is no transparency between the foundation and the donors. Based on that previous statement, it is able to cause a donor to distrust to keep donating. There are many things occurred there, such as recording of revenue transactions and expenses amount that have not been well organized. Currently, it has not provided a facility that allows donors to donate. In addition, it has not been maximized in utilizing the ICT development that covers two aspects; they are information of technology and communication technology. Solutions for solving existing problems by designing a donation system of web-based in using waterfall method in accordance with five steps; those are requirement, design, implementation, verification, and maintenance. The results and benefits of this web-based donation system provide the ease for donors so that transactions can be made by utilizing the internet as technology. It also creates transparency of financial report that can be seen and monitored by donors.